Contingency management strategies of the Nursing Department in centralized rescue of patients with coronavirus disease 2019 - Huafen Wang; Jiehui Feng; Lewen Shao; Jianhua Wei; Xiaoyan Wang; Xiaowei Xu; Rongya Shao; Meiyun Zhang; Jiangjuan He; Xuehong Zhao; Tingbo Liang (International Journal of Nursing Sciences, 2020)
Objectives: This article aims to summarize a series of contingency management strategies of the Nursing Department in the centralized treatment of patients with coronavirus disease 2019 (COVID-19). Methods: The strategies of the Nursing Department included an early warning for prevention and control, taking functions of vertically commanding and horizontally coordinating, and reasonably allocating nursing workforce, to facilitate centralized treatment work in the in-hospital fever clinic, isolation wards and ICU, and referral and admission of critical patients. Five special groups were established in charge of training and examination, management and supervision, psychological support, logistical support, and reporting and publicity, respectively. Results: It was achieved that no deaths from critical patients and no medical staff, no other patients were infected. Conclusion: Through the implementation of these strategies, safe and efficient centralized treatment was ensured timely, orderly and sustainably.